Mapeamento da pesquisa no campo da formação de professores de química no Brasil (2000-2010) - Silva, Osmair Benedito da (2013)
The purpose of this paper is to map out academic production in the form of theses and dissertations on the topic of chemistry teacher education, submitted to graduate programs in chemistry, education, and teaching of science and mathematics in Brazil (CAPES areas 4, 38, and 46), between 2000 and 2010. To this end, 33 doctoral theses and 104 master s dissertations were analyzed in their entirety based on the following descriptors: year of submission, academic level or title, geographic region, institution and graduate program of origin, supervisor and author, education, theme, and academic genre. Results from this study suggest the consolidation of the field of research on chemistry teacher education in Brazil in view of the growth in academic production within the period under investigation. Dissertations were found in all geographical regions of the country. Regarding the institution of origin, USP ranked first in the number of studies (20.5%), followed by UFRN (7.5%), UNESP at Bauru (5.8%), and UFSCar (4.4%). Despite its growth, results also show that in most regions, especially in the North, research in this field is rather frail and erratic, which indicates the need to establish new research groups. As for publications derived from dissertations and theses, 194 papers, 87 articles, 17 book chapters, and seven books were produced. The most frequently addressed educational levels were: higher education (54.6%) and high school (36.5%), while the most recurrent research themes were preservice teacher education (56.2%) and inservice teacher education (24.1%). At lesser proportion, there were found studies on teacher identity and professionalization (9.5%) and teaching pedagogical practice (3.6%). With respect to preservice teacher education, the most recurring topics involved teacher education programs, whereas with regard to inservice education, the ones related to teachers conceptions were favored. The preferred academic genre was research. The most commonly employed research methodology was qualitative in nature, predominantly anchored in content analysis and case studies. Therefore, the aim of this study was to contribute to the ongoing debate on chemistry teacher education in Brazil and pose questions concerning existing and future research conducted on this subject.